Adaptasi Human Machine Interface (HMI) dalam Monitoring dan Kendali Kualitas Air pada Tambak Udang - Maman Somantri; M Arfan; Oscar Solideo Siregar (Universitas Diponegoro, 2022)
A good and really important vaname cultivation is to maintain the quality of shrimp. Shrimp pond water quality includes several parameters including temperature, pH, salinity, oxygen content, and air altitude. The large number of actuators and sensors requires an interface that connects sensors and actuators with humans to facilitate the monitoring process and manual remote control. In this study, a web-based Human Machine Interface (HMI) was built to monitor and control air quality manually remotely. The HMI built in this research uses IoT (Internet of Things) technology so that the process of reading and sending data can be done anywhere, anytime, and through any online device. This website-based HMI was tested using the black box testing method, namely by looking at the experimental results based on the given scenario. The survey results were also given to 5 respondents, 2 of whom considered this website-based HMI to be very good and 3 others considered it normal. From this test, it can be said that the website-based HMI has been successfully implemented